2019
DOI: 10.3390/polym11060947
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of Metal-Organic Framework Materials as Controlled-Release Fertilizers in Crop Fields

Abstract: The behavior of a metal-organic framework (MOF) compound synthesized in hydrothermal reaction conditions and rich in N, P, and Fe nutrients was explored in the field. The attenuated total reflection-Fourier transform infrared (ATR-FTIR) spectroscopy and laser induced breakdown spectroscopy (LIBS) characterization results showed that the chemical structures changed during the degradation process in crop field soil. The scanning electron microscope images showed that the micro-rod of the MOF peeled off and degra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 37 publications
0
26
1
Order By: Relevance
“…6C). Compared to previously reported nutrient release rates (in compounds using oxalic acid as ligands), 32 the compounds reported here showed higher nutrient release rates. This result is likely due to the difference between ligands.…”
Section: Resultscontrasting
confidence: 93%
See 1 more Smart Citation
“…6C). Compared to previously reported nutrient release rates (in compounds using oxalic acid as ligands), 32 the compounds reported here showed higher nutrient release rates. This result is likely due to the difference between ligands.…”
Section: Resultscontrasting
confidence: 93%
“…The results revealed that the MOF material degraded by 50.9% throughout a wheat season, and exhibited a slow nutrient release rate. 32 Although these materials show potential as controlled-release fertilizers, they are low in N content, which is likely to limit their application in agriculture. Therefore, in this work, we chose an eco-friendly organic ligand and developed two novel MOFs with relatively high nutrient contents.…”
Section: Introductionmentioning
confidence: 99%
“…The X-ray powder diffraction spectra of compounds I, II, and III were compared with reference OPA-MOF [ 10 ] ( Figure 1 ) and the data of the international diffraction data center. It is found that the three compounds were new phases with crystallinity of 92.28%, 96.72%, and 93.97%, respectively.…”
Section: Resultsmentioning
confidence: 99%
“… X-ray powder diffraction spectra of MOFs (compounds I, II, and III) and reference oxalate phosphate amine metal organic framework (OPA-MOF) [ 10 ]. …”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation